2015
DOI: 10.3109/13697137.2014.1001357
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lower concentrations of phytoestrogens on the effects of estradiol in breast cancer cells

Abstract: This study demonstrates that, in the presence of E2, genistein, resveratrol, and quercetin may stimulate breast cancer cells, even at low physiological concentrations. Therefore, the conflicting results regarding the effects of phytoestrogens on breast cells may be attributed to the endogenous estrogen present in breast tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Thus, the effects of phytoestrogens were mainly proven in human breast cancer cell lines. In addition to other studies, our previous study demonstrated that genistein, resveratrol and quercetin do not stimulate MCF‐7 breast cancer cells and may induce apoptosis even at low concentrations . However, cancers are well known for high heterogeneity .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Thus, the effects of phytoestrogens were mainly proven in human breast cancer cell lines. In addition to other studies, our previous study demonstrated that genistein, resveratrol and quercetin do not stimulate MCF‐7 breast cancer cells and may induce apoptosis even at low concentrations . However, cancers are well known for high heterogeneity .…”
Section: Discussionmentioning
confidence: 76%
“…The present study confirmed the apoptosis effects of these phytoestrogens at general physiological concentrations in primary breast cancer cells, as well as in breast cancer cell lines. Furthermore, these phytoestrogens also inhibit cell viability in primary breast cancer cells, which was not significant in MCF‐7 breast cancer cell lines …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…ERα expression is significantly induced by E 2 regardless of the presence of these phytoestrogens, although resveratrol is reported to have estrogen‐like activity in a transcriptional assay in cells overexpressing ER . Genistein, resveratrol, and quercetin may stimulate the proliferation of breast cancer cells, even at low physiological concentrations (at concentrations ≥ 10 –6 M) when E 2 is present . Therefore, the conflicting results regarding the effects of phytoestrogens on breast cancer cells may be attributed to the endogenous estrogens present in breast tissue …”
Section: The Interactions Between Steroid Hormones and Resveratrolmentioning
confidence: 99%
“…Among many bioactive natural compounds, genistein and resveratrol have been the most widely studied, and reports showed that both compounds inhibited estrogen-induced DNA synthesis and proliferation of ER-positive breast cancer cells [317326]. However, genistein and resveratrol could differently modify ERE-dependent transcription and expression of ERE-mediated genes, such as ER, PR, and pS2/Trefoil factor 1(TFF1) in the presence and absence of estrogen [97, 270, 319, 324327]. These effects of genistein and resveratrol could be mediated through both ER-dependent and ER-independent pathways.…”
Section: Bioactive Natural Products Targeting Estrogen-mediated Mementioning
confidence: 99%